A simplified method for seismic assessment of unreinforced masonry buildings. Issue 1 (2nd January 2022) - Capanna, I.; Di Fabio, F.; Fragiacomo, M.
ABSTRACT: The paper presents a simplified vulnerability assessment method for unreinforced masonry buildings based on the evaluation of a few structural parameters, which can be determined from visual inspection and a geometry survey. The authors proposed an empirical approach with the aim to assess the in-plane vulnerability quickly by predicting the damage failure of bearing masonry walls. Field observations reveal different behaviours: out-of-plane and in-plane seismic responses. Several simplified assessments focus on out-of-plane behaviour. Few studies deal with in-plane seismic behaviour, which is also the expected response for more masonry buildings. The proposed seismic method provides a vulnerability index, which is evaluated as the weighted sum of 10 parameters markedly affecting the in-plane seismic performance. The reliability of the method is investigated through an application on buildings located in Central Italy, damaged by the 2016 earthquake. The mean damage and damage probability distributions were predicted for each building using the proposed method. Then, fragility functions were estimated from the results of non-linear static analysis, and the damage probability distributions were derived. The capability of the simplified method to foresee the damage probabilities was confirmed by a comparison between different approaches, confirming the reliability of the method in large-scale seismic assessment.